2012
DOI: 10.1007/s12975-012-0200-y
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Like Property Profiling of Novel Neuroprotective Compounds to Treat Acute Ischemic Stroke: Guidelines to Develop Pleiotropic Molecules

Abstract: The development of novel neuroprotective compounds to treat acute ischemic stroke (AIS) has been problematic and quite complicated, since many candidates that have been tested clinically lacked significant pleiotropic activity, were unable to effectively cross the blood brain barrier (BBB), had poor bioavailability or were toxic. Moreover, the compounds did not confer significant neuroprotection or clinical efficacy measured using standard behavioral endpoints, when studied in clinical trials in a heterogeneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 95 publications
(134 reference statements)
1
8
0
Order By: Relevance
“…Several studies have reported the lack of mutagenic action for many classes of chalconas [ 38 , 39 ]. Furthemore, in a study using diferent hydroxychalcones, 4’5’-dimethyl-2’,3,4-trihydroxylchalcone, 6 methyl-2’,3,4-trihydroxychalcone, and 3,3’,4’,7-tetrahydroxyflavone, none of them presented mutagenic effect by the Ames test [ 40 ]. Also in our study, all the doses of 2HMC exhibited MI lower than the negative control (MI = 1.00) in both tester strains, indicating a possible toxic effect of this chalcone in S .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the lack of mutagenic action for many classes of chalconas [ 38 , 39 ]. Furthemore, in a study using diferent hydroxychalcones, 4’5’-dimethyl-2’,3,4-trihydroxylchalcone, 6 methyl-2’,3,4-trihydroxychalcone, and 3,3’,4’,7-tetrahydroxyflavone, none of them presented mutagenic effect by the Ames test [ 40 ]. Also in our study, all the doses of 2HMC exhibited MI lower than the negative control (MI = 1.00) in both tester strains, indicating a possible toxic effect of this chalcone in S .…”
Section: Discussionmentioning
confidence: 99%
“…However, quantification of TUNEL positive neurons would have certainly strengthened our hypothesis. Further studies are necessary for clinical translation (Bahjat et al, 2013; Lapchak, 2013; Tajiri et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…The development of a CNS-active drug to treat stroke requires special attention since they must be able to cross the blood-brain barrier (BBB) to penetrate into the penumbra. This can be taken into consideration when developing molecules using the Lipinski rules as well as utilizing BBB penetration assays (in vitro) for primary candidate selection and then in vivo for drug development [8284]. Moreover, during the initial stages of drug development, rapid and cost-effective toxicity screens (CeeTox and micronucleus assays) can help eliminate compounds with excessive unwanted “side effects”.…”
Section: The Rigorous Path To Demonstrate Neuroprotection: Animal Modelsmentioning
confidence: 99%